The impact of online learning quality service on students online learning satisfaction - Hidayat, Riyan; Armansah, Youdi; Syed Aris, Sharipah Ruzaina; Imami, Muh Khairul Wajedi; Walad, Muzakkir; Al-inayah, Cindhy Rizkika (Zenodo, 2024)
The current research aims to examine the impact of online learning service quality on student online learning satisfaction. The participants were determined through the purposive sampling method. A total of 158 university students participated in the current research. The participants were given questionnaires related to online learning quality service and student online learning satisfaction. The data gathered will then be analyzed in the statistical package for social science (SPSS), employing several analyses, namely descriptive analysis, Pearson correlation coefficient, and multiple regression analysis. The descriptive analysis concludes that the level of online learning service quality and students' satisfaction in online learning settings were very high. The Pearson correlation indicates a strong and significant correlation between online learning quality service and student online learning satisfaction. The result of the multiple regression analysis emphasized the significant impact of the online learning quality service on student online learning satisfaction, where three dimensions of online learning quality service significantly contributed to student online learning satisfaction, namely internet self-efficacy, technology quality, and convenient usage. This research contributed to proving the impact of online learning quality service on student online learning satisfaction. This research also predicts several aspects of online learning service quality that significantly affect students online learning satisfaction